ANALISA KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA DI SMK TERPADU YASPIDA KABUPATEN SUKABUMI - Fitri Yudiati (BUANA INFORMATIKA, 2016)
Schools which are a place for education and students are the main consumers in schools need to be given important priority, especially in terms of service, students usually prefer to discuss their dissatisfaction with the performance and service of employees at this school with only the students themselves. This is because the school environment is closed or indeed from the ignorance of the students in conveying their complaints.The population in this study was from 6049 students at SMK Terpadu Yaspida, the determination of the sample from the population was 269 respondents, namely students. The results showed that performance and service had a significant effect on student satisfaction, this was proven by the thit value for performance was 165.299 and the ttab value (dk = 269-2-1 =266, = 5%) = 1.980, so thit > ttab (165.299 > 1.980) and based on the results of the analysis it is known that Haaccepted, meaning that performance and service significantly influence student satisfaction.